Development, implementation and evaluation of a pain management and palliative care educational seminar for medical students - Paneduro, Denise (Pulsus Group Inc, 2014)
BACKGROUND: Despite calls for the development and evaluation of pain education programs during early medical student training, little research has been dedicated to this initiative. OBJECTIVES: To develop a pain management and palliative care seminar for medical students during their surgical clerkship and evaluate its impact on knowledge over time. METHODS: A multidisciplinary team of palliative care and pain experts worked collaboratively and developed the seminar over one year. Teaching methods included didactic and case-based instruction, as well as small and large group discussions. A total of 292 medical students attended a seminar during their third- or fourth-year surgical rotation. A 10-item test on knowledge regarding pain and palliative care topics was administered before the seminar, immediately following the seminar and up to one year following the seminar. Ninety-five percent (n=277) of students completed the post-test and 31% (n=90) completed the follow-up test. RESULTS: The mean pretest, post-test and one-year follow-up test scores were 51%, 75% and 73%, respectively. Mean test scores at post-test and follow-up were significantly higher than pretest scores (all P<0.001). No significant difference was observed in mean test scores between follow-up and post-test (P=0.559), indicating that students retained knowledge gained from the seminar. CONCLUSIONS: A high-quality educational seminar using interactive and case-based instruction can enhance students’ knowledge of pain management and palliative care. These findings highlight the feasibility of developing and implementing pain education material for medical students during their training.